Computer Oriented Mathematical Models for Chemical System - Rao, G.Nageswara; Satyanarayana Rao, S.V.V.; Ravindra Babu, A.; Sambasiva Rao, R. (Asian Journal of Chemistry, 2010)
The applications of computers to chemical problems are as wide and deep as chemistry itself. Advances in instrumentation, information science etc., resulted in chemometrics. Commonly occurring mathematical models applicable in various chemical problems are emphasized. Apart from direct solutions, application of iterative methods in solvent extraction equilibrium is given. Importance of simulated data and experimental optimization is indicated.